Analysis For Condemnation Aspect Of Fine In The Enforcement Of Traffic Law No. 14 Year 1992 In Medan Municipalyty: Analysis For Condemnation Aspect Of Fine In The Enforcement Of Traffic Law No. 14 Year 1992 In Medan Municipalyty - Humala Simangunsong (Institute Of computer Science (IOCS), 2019)
Comdemnation of traffic fine will be more useful when the enforcement is adjusted to the current idea in the community of Indonesia. Therefore to make sure the construction in addition to light up law and justice based on ideology of Pancasila, the discussion and research comdemnation sanction of fine containing renewal elements need for light up the norms of penal law need to be performed by researchers or law experts, so that the harmony betwen sanction and the content of the penal law can be feeling. Traffic law No.14 / 1992 is guideliness for the community about how the norms of traffic in high in higway. This research is intended to find the truth rationally and empirically a correctness about the existence of application in fine comdemnation of traffic in the Municipality of Medan, and then it is also aimed at identify the obstacles and the opportunity of the success in fine comdemnation system enforced by using deposition of money. The collection of data in the study was performed by using the primary and secondary methods. The primary method was used to collect data which involved the documentation and questionary method, while the secondary method was used in collection the data in addition to fine the more complete information by using observation and interview. Based on the methods used in examining and process the data, then it could be a conclussion which was proved by the analysis for the results of the research by considering the normative qualitative approach. The basic of analisys which was used was the rule of traffic law and transfortation of highway as well as the other rules related to fine condemnation. The results of the research showed that the effectivity in the enforcement of fine comdemnation of traffic and transportation No. 14 / 1992 could be reached when it was adjusted to the current idea in the community of Indonesia. Therefore, nowdays is the present time is most appropriate to socialize the fine comdemnation by deposition, because of this system is very actually suitable to the responsibility spirit of quality in article 1367 of Civil Code.